Differentiated Approach in the Innovative Teaching - Maryna Prokof'yeva (Pedagogical Discourse, 2011)
The definition „differentiated approach” in pedagogical scientific thought is theoreticaly analyzed, reference points of application of the differentiated approach under the context of innovative education are revealed.